Kontury máchovského mýtu - Faktorová, Veronika (Wydawnictwo Rys (nr 1); Wydawnictwo Naukowe UAM (nr 2), 2011)
In 2010, Czech culture celebrates the 200-year anniversary of the birth of Karel Hynek Mácha, the Czech romantic poet. The early reactions to Mácha´s works were for the most part rejections: national culture did not want to admit themes that would not serve the immediate goal of developing Czech patriotic culture. In despite of this, from the 1860´s, Mácha´s legacy gradually advanced into the focus of Czech culture. Nevertheless, Mácha can be seen as indisputable part of the Czech cultural canon from the late nineteenth century. The ways in which Mácha became the greatest inspiration appearing in Czech literature, music, visual ATS, films or theatre were different, although they all created the mythological interpretations of poet.
Contours of Mácha´s myth
Keywords: Mácha; cultural canon; mythological interpretation; patriotic culture; art inspirations